2021
DOI: 10.3390/atmos13010042
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in Terrestrial Vegetation and Carbon Fluxes under 1.5 °C and 2.0 °C Global Warming

Abstract: The terrestrial ecosystem plays a vital role in regulating the exchange of carbon between land and atmosphere. This study investigates how terrestrial vegetation coverage and carbon fluxes change in a world stabilizing at 1.5 °C and 2 °C warmer than pre-industrial level. Model results derived from 20 Earth System Models (ESMs) under low, middle, and high greenhouse emission scenarios from CMIP5 and CMIP6 are employed to supply the projected results. Although the ESMs show a large spread of uncertainties, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, high temperatures beyond the plant tolerance threshold can increase plant respiration and inhibit photosynthesis (Salvucci and Crafts-Brandner, 2004). Some studies have shown that temperature extremes may decrease the plant productivity and change the carbon cycle of the ecosystem through affecting plant physiological processes (Meehl et al, 2000;Smith et al, 2009;Frank et al, 2015;Piao et al, 2019;Peng et al, 2022). For example, the heat wave event occurring in western Russia in 2010 led to a significant decrease in local ecosystem productivity (Bastos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, high temperatures beyond the plant tolerance threshold can increase plant respiration and inhibit photosynthesis (Salvucci and Crafts-Brandner, 2004). Some studies have shown that temperature extremes may decrease the plant productivity and change the carbon cycle of the ecosystem through affecting plant physiological processes (Meehl et al, 2000;Smith et al, 2009;Frank et al, 2015;Piao et al, 2019;Peng et al, 2022). For example, the heat wave event occurring in western Russia in 2010 led to a significant decrease in local ecosystem productivity (Bastos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in temperate regions, CMIP6 models overestimate tree height, which may lead to overestimating aboveground carbon storage and underestimating wind speed (Song et al 2021). However, in both CMIP5 and CMIP6 models, leaf area index is projected to increase in virtually all biomes worldwide under scenarios of 1.5˚C and 2˚C warming above pre-industrial levels (Peng et al 2022).…”
Section: Projections Of Future Climate and Effects Of Climate Changementioning
confidence: 99%